(untitled) (Journal of the College of Basic Education, 2022)
Dialogue is an important feature of fictional literature, as it represents the real interface of the modern novel, as that novel worked to highlight the role of dialogue and exaltation, especially the internal dialogue (the monologue), which was borrowed from foreign novels that focused on a subject and made it at the forefront of other elements of the novel.